Frontiers in nano-therapeutics - Tasnim, Nishat; Nair, Baiju G.; Krishna, Katla Sai; Kalagara, Sudhakar; Narayan, Mahesh; Noveron, Juan C.; Joddar, Binata (Springer, 2017)
This brief highlights recent research advances in the area of nano-therapeutics. Nanotechnology holds immense potential for application in a wide range of biological and engineering applications such as molecular sensors for disease diagnosis, therapeutic agents for the treatment of diseases, a vehicle for delivering therapeutics and imaging agents for theranostic applications, both in-vitro and in-vivo. The brief is grouped into the following sections namely, A) Discrete Nanosystems ; B) Anisotropic Nanoparticles; C) Nano-films/coated/layered and D) Nano-composites.
Keywords: Nanomedicine -- Therapeutic use.; elektronické knihy; electronic books